URGENSI DAN KESALAHAN DALAM MA’RIFATULLAH - Suryati Suryati (Wardah, 2011)
Ma `rifatullah is part of Islamic teaching to be done by all the servants of Allah Almighty, because ma` rifatullah aims to recognize, believe, and worship only Him infinitely precious substance.Know Allah is perfectly able to deliver positive change in both the servant and batiniyah zhahiriyah. Zhohiriyah changes will be seen from the physical motion of a servant to the Oneness of God, and while it batiniyah changes will be seen from a non-physical behavior for the worship of Allah SWT. Thus a servant who always know God, and know the name, and all his properties, then it can become a servant of his faith strong and sturdy, and it would be to have a religious spirit and sincerity.